The formation of a conceptual model of the concept of" chemical processes - Shaposhnyk, A. M. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the problem of the effective training of future specialists chemical profile on the basis of formation of conceptual thinking. It was determined that the formation of scientific concepts system creates conditions for the development of the scientific way of thinking of the future specialist. It was found that the formation of concepts is accompanied by the release of the essential features of the content of the concept, the establishment of relationships between concepts, generalization of the image-spatial, verbal speech, subject and other components. Revealed, that between concepts can form logical, functional, serial communications, and communications "partwhole", "cause-effect", "item-set" and others. The conceptual model of the concepts of "chemical processes", "homogenous chemical processes "" heterogeneous chemical processes. » The basis of the model of semantic features was used. For these concepts defined set of features appointment, composition and structure, the principle and mechanism of action, characteristics and parameters. It was established that these conceptual models of concepts characterized by the presence of functional links and relations "part-whole", "item-set".